1998
DOI: 10.1177/172460089801300305
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Specific Enolase in Non-Neoplastic Lung Diseases, a Marker of Hypoxemia?

Abstract: Neuron-specific enolase (NSE) is a glycolytic enzyme localized within neuronal and neuroendocrine tissues. Serum NSE is widely used as a marker of neuroendocrine tumors. Moderate serum NSE elevation has been reported in some patients with benign lung diseases. We decided to investigate whether the elevation of serum NSE in non-neoplastic lung diseases is connected with hypoxemia and to what extent the recovery of sufficient ventilation with a respirator may influence NSE concentrations. Serum NSE was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The most striking transcriptional induction in our data has been determined for ENO2, whose gene product converts phosphoglycerate to phophoenolpyruvate, with a fold change expression of 177. ENO2 has been known for a while to be inducible by hypoxia (Szturmowicz et al, 1998), and its upregulation has been determined in murine melanoma cells (Olbryt et al, 2006), human cord blood and bone marrow mesenchymal stem cells (Martin-Rendon et al, 2007), as well as in adipocytes (Mazzatti et al, 2012) but not to the extent as revealed by our data. In view of our binding site analysis and the striking transcriptional attenuation after HIF-1 inhibition we conclude that HIF-1α directly binds the ENO2 promoter and therefore is responsible for their mRNA upregulation in adipocytes.…”
Section: Discussionmentioning
confidence: 48%
“…The most striking transcriptional induction in our data has been determined for ENO2, whose gene product converts phosphoglycerate to phophoenolpyruvate, with a fold change expression of 177. ENO2 has been known for a while to be inducible by hypoxia (Szturmowicz et al, 1998), and its upregulation has been determined in murine melanoma cells (Olbryt et al, 2006), human cord blood and bone marrow mesenchymal stem cells (Martin-Rendon et al, 2007), as well as in adipocytes (Mazzatti et al, 2012) but not to the extent as revealed by our data. In view of our binding site analysis and the striking transcriptional attenuation after HIF-1 inhibition we conclude that HIF-1α directly binds the ENO2 promoter and therefore is responsible for their mRNA upregulation in adipocytes.…”
Section: Discussionmentioning
confidence: 48%
“…It regulates the steady-state concentration of 2,6-bisphosphate, an allosteric activator of phosphofructokinase. Like PFKP and ENO2, it is activated by hypoxia as well [ 3 , 18 , 19 , 20 ]. In metabolic screens PFKFB4 has been proposed as a new potential target in cancer therapy as its silencing increased the ROS level and inhibited survival of cancer cells but not epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 Expressions of nine of the upregulated genes, IGFBP-3, ADM, ANGPTL4, PLOD2, DSIPI, NDRG1, ENO2, HIG2 and BNIP3L, has been reported previously to be induced by hypoxia. 26,[29][30][31][32][33][34][35][36][37][38] We hypothesize that ZD6474 inhibits neovascularization in tumors, thereby limiting the oxygen and nutrient supply and resulting in tumor hypoxia and upregulation of hypoxia-inducible genes. If this hypothesis is correct, hypoxiaregulated genes and gene products might be useful biomarkers for the pharmacodynamic effects of ZD6474 and other antiangiogenic agents in preclinical and clinical settings.…”
Section: Discussionmentioning
confidence: 99%